An Optimal Electric Dipole Antenna Model and Its Field Propagation - Yidong Xu; Lili Guo; Wei Xue; Korochentsev Vladimir; Junwei Qi (International Journal of Antennas and Propagation)
An optimal electric dipole antennas model is presented and analyzed, based on the hemispherical grounding equivalent model and the superposition principle. The paper also presents a full-wave electromagnetic simulation for the electromagnetic field propagation in layered conducting medium, which is excited by the horizontal electric dipole antennas. Optimum frequency for field transmission in different depth is carried out and verified by the experimental results in comparison with previously reported simulation over a digital wireless Through-The-Earth communication system. The experimental results demonstrate that the dipole antenna grounding impedance and the output power can be efficiently reduced by using the optimal electric dipole antenna model and operating at the optimum frequency in a vertical transmission depth up to 300 m beneath the surface of the earth.